PEMANFAATAN LIMBAH AMPAS TEBU SEBAGAI PENGGANTI FILLER UNTUK CAMPURAN ASPAL BETON JENIS “HOT ROLLED SHEET– WEARING COURSE“ - Fajar Himawan Wijanarko; Moh. Bachtiar Mulia; YI. Wicaksono; Djoko Purwanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Highway pavement in Indonesia generally use a mix asphalt concrete as a surface layer consisting of a mixture of constituent materials coarse aggregate, fine aggregate, filler and bitumen. HRS is a mixture suitable for use in tropical areas like Indonesia because it has high elasticity and resistance to fatigue plastic (Rantetoding, 1984). HRS mixture consists of coarse aggregate, fine and asphalt. Fine aggregate form filler, which is necessary to fill voids between the aggregate particles so as to increase the density of the mixture. In general filler used is stone ash, stone ash filler but is relatively expensive, so it is necessary to find other alternatives to the use of cheaper materials for filler substitutes standard. One of the waste materials that can be used is the waste from sugar mills bagasse. Refiners produce waste in the form of bagasse, the percentage content of chemical compounds (Silica) on bagasse ash was 70.94% which is expected to improve the quality of asphalt mix. The purpose of this research is to determine the performance of asphalt concrete type of HRS-WC when using bagasse ash filler compared with stone ash filler, with the goal of getting an alternative filler in the form of bagasse ash. Test characteristics of aggregate, filler and bitumen done before making Marshall specimens to determine whether the materialis qualified or not as asphalt mix material. This study refers to the Spesifikasi Umum Bina Marga 2010, of the Directorate General of Highways. The results showed the test aggregate, filler and bitumen, as well as all the HRS-WC mixed with bagasse ash filler and stones ash filler qualify. The use of bagasse ash filler mixed with HRS-WC increasing bitumen content is 6.95%, resulting in values, VIM: 5.96%, VMA: 21:36% and VFB: 72.12%, is higher than the HRS-WC mixture using stones ash filler that is 6.75%, with a value of VIM: 5.95%, VMA: 20.64% and VFB: 71.68%. In addition to the value of bagasse ash filler Stability: 1231.07 Kg, Marshall Quotient: 260.58 Kg / mm and flow: 4.72 mm being lower than the value of Stability: 1280.98 Kg, Marshall Quotient: 268.97 Kg / mm and flow: 4.76 mm in stone ash filler. This suggests that the HRS-WC mixture using bagasse ash filler bitumen requires more than the HRS-WC mixture using stone ash filler. From the results of this analysis indicate that the use of bagasse ash filler mixed with HRS-WC to qualify as an alternative filler materials stone ash, so that the bagasse ash can be used for asphalt concrete mix HRS-WC, in which the results are not much different from mixed HRS-WC using stone ash filler.